Integrasi Pendidikan Islam dan Pembelajaran Kewirausahaan di Pesantren Minoritas Muslim - Wekke, Ismail Suardi (FENOMENA, 2017)
Pesantren (boarding school) in Indonesia educational system proofs a significant contribution. They participate in enhancing teaching and learning and extending the processes of acquiring knowledge with the spirit of Islam. These activities spread out through the nation-wide, include some part of Papua island. Therefore, it is a need to explore the practice of Islamic education, expecially muslim minority. In addition, the religious based institution will have less culture support and different environment from other majority. A qualitative approach was employed to conduct this research. In-depth inteview and non-participant observation were implemented during data collection. There are four pesantrens were observed, they are Pesantren Nurul Yaqin, Pesantren Roudhotul Khuffadz, Pesantren Minhajut Tholibin, and Pesantren Hidayatullah. All the site are located in Sorong regency. Research findings shows that in elaborating learning process in pesantren to accelerate studentsâ skill is impelementation of entrepeneurship. After school duration, extracurriculer is running to maintain the learning outside classroom. The students still have opportunity to learn not only in the classroom but also they will participate in the real space. The extension of classroom to the field is an effort to relate theoretical attainment to skills development. Those institutions executed this kind of program due to limited time in practice for subject matter on time allocation. Finally, pesantren is not solely the place to learn religion. Management board tried to encourage students in participating the entrpreneurship based various activities to complement studentsâ skills after graduating from the Islamic school.